A NEW FRONTIER: THE CHALLENGES SURROUNDING THE DEEPENING IMPACT OF DATA PROTECTION REGULATIONS ON BANKRUPTCY LAW - Tajti, Tibor (Pravni zapisi, 2023)
Notwithstanding the unprecedented and global prestige that data privacy (or data protection, in Europe) law has gained in the 21st century, comparative analyses of the effects flowing from the intensifying impact of data protection law on bankruptcy (insolvency) law remain unexplored. In addition to canvassing the history and contours of the data protection–bankruptcy law interface, through an empirical com- parison of available court and data protection agency (authority) cases in multiple jurisdictions, this article fills this gap by identifying and exemplifying various modalities through which data protection law interferes with the bankruptcy process or creates tensions between the two branches of law, based on the comparison of available court and data protection authority (agency) cases in Europe (including the United Kingdom), the United States, as well as Canada and China, as middle-ground systems.
Keywords: Bankruptcy (Insolvency) Law; Data Protection (Privacy); Recast EU Insolvency Regulation 2015/848; European e-Justice Portal; Interconnected Insolvency Registries; Red Tape; Middle-Ground Systems